Modeling and dynamic response of double-feed induction generator and back-to-back converters in unbalanced grid voltage conditions. Issue 4 (August 2020) - Mirzakhani, Ali; Ghandehari, Reza; Davari, S Alireza
Double-feed induction generators are one of the most commonly used generators in wind power plants. Therefore, studying this type of generators in different grid conditions such as unbalanced grid voltage is of great importance. In this article, double-feed induction generators, in synchronous reference frame, and back-to-back converters are reviewed and modeled. The advantage of this model, compared with previous ones, is that it can be used in unbalanced grid voltage conditions. Hence, different parts of the generator in synchronous positive reference frame are studied and governing equations in such conditions are analyzed. Stator output power, rotor side converters, grid side converters, and electromagnetic torque, mentioned in the model, are analyzed, as well. The model is also applied in balanced conditions. Therefore, the model proposed in this article is perfect for analyzing wind turbine-based power plants with double-feed induction generators. The accuracy of the suggested function was confirmed through simulation.